Rehabilitation of Neuromuscular Diseases During COVID-19: Pitfalls and Opportunities - Liguori, Sara; Moretti, Antimo; Paoletta, Marco; Gimigliano, Francesca; Iolascon, Giovanni (Frontiers in Neurology, 2021)
The outbreak of COVID-19 caused by SARS-CoV-2 has spread worldwide with a huge impact on the healthcare system. Compared to the previous coronaviruses-related pandemics, the COVID-19 is more transmissible with a potential systemic involvement and peculiar neurological manifestations, such as Guillan-Barrè syndrome up to critical illness myopathy, occurring in the intensive care setting. In this clinical scenario, people living with a neuromuscular disease (NMD) represent a vulnerable category with a high risk of severe course of COVID-19. Moreover, in the NMD population, the management of respiratory and muscular impairments after SARS-CoV-2 infection might be troubling, both in terms of pharmacological and rehabilitative approaches. To date, rehabilitation is still an unmet need in this population with several implications on NMD progression, with and without SARS-CoV-2 infection. In particular, rehabilitation intervention for patients with NMD after COVID-19 are lacking. Therefore, in the current paper, we analyze the critical issues of COVID-19 on NMDs patients and propose a home-based rehabilitation program targeted for this population after mild to moderate SARS-CoV-2 infection.